2020
DOI: 10.1534/g3.120.401309
|View full text |Cite
|
Sign up to set email alerts
|

CeMbio - TheCaenorhabditis elegansMicrobiome Resource

Abstract: The study of microbiomes by sequencing has revealed a plethora of correlations between microbial community composition and various life-history characteristics of the corresponding host species. However, inferring causation from correlation is often hampered by the sheer compositional complexity of microbiomes, even in simple organisms. Synthetic communities offer an effective approach to infer cause-effect relationships in host-microbiome systems. Yet the available communities suffer from several drawbacks, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
226
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(237 citation statements)
references
References 78 publications
11
226
0
Order By: Relevance
“…Previous studies have assessed the natural C. elegans microbiota [18] by isolating and cultivating nematodes in decaying organic matter, and have isolated native bacterial strains by grinding the naturally colonized worms [30][31][32]45]. We isolated new bacterial strains from worms with a similar protocol (CR collection, Methods) and also utilized the MYb collection from Dirksen et al [32,60] which contains some of the bacteria persistently found in the C. elegans gut. From these two collections, we selected a phylogenetically diverse set of bacterial isolates, spanning four different phyla, to study the colonization patterns of native bacteria (Fig.…”
Section: Three-species Microbiotas Are Predicted By Pairwise Outcomesmentioning
confidence: 99%
“…Previous studies have assessed the natural C. elegans microbiota [18] by isolating and cultivating nematodes in decaying organic matter, and have isolated native bacterial strains by grinding the naturally colonized worms [30][31][32]45]. We isolated new bacterial strains from worms with a similar protocol (CR collection, Methods) and also utilized the MYb collection from Dirksen et al [32,60] which contains some of the bacteria persistently found in the C. elegans gut. From these two collections, we selected a phylogenetically diverse set of bacterial isolates, spanning four different phyla, to study the colonization patterns of native bacteria (Fig.…”
Section: Three-species Microbiotas Are Predicted By Pairwise Outcomesmentioning
confidence: 99%
“…While we highlight mouse models above, many additional organisms serve as powerful laboratory systems to reveal insights into the relationship between the microbiome and host transcription. Studies conducted in zebrafish (Murdoch and Rawls 2019), C. elegans (Dirksen et al 2020;Yang et al 2019), and Drosophila melanogaster (Broderick et al 2014;Douglas 2018;Elya et al 2016) for example, all have revealed the impact of the microbiome on immunity, metabolism, and developmental gene regulation.…”
Section: Relationship Between Microbiome and Gene Expression In Modelmentioning
confidence: 99%
“…We also sought to model the functional redundancy observed in natural communities by including several taxonomically related bacterial strains from distinct wild C. elegans strains or habitats (range of 2-22 strains). BIGbiome complements simplified microbiomes like the recently developed 12-member CeMbio community 20 as it reflects the extensive strain level microbial diversity found in C. elegans natural microbiomes while still remaining experimentally tractable.…”
Section: Resultsmentioning
confidence: 99%